1-Aminocyclopropane-1-carboxylic acid deaminase producing beneficial rhizobacteria ameliorate the biomass characters of Panicum maximum Jacq. by mitigating drought and salt stress. Issue 1 (December 2018) - Tiwari, Garima; Duraivadivel, P.; Sharma, Satyawati; P., Hariprasad
Abstract 1-Aminocyclopropane-1-carboxylic acid (ACC) is a precursor molecule of ethylene whose concentration is elevated in the plant subjected to biotic and abiotic stress. Several soil microorganisms are reported to produce ACC deaminase (ACCd) which degrades ACC thereby reducing stress ethylene in host plants. This study is aimed to apply ACCd producing beneficial rhizobacteria to improve biochemical parameters and cell wall properties ofPanicum maximum exposed to salt and drought stress, focusing on bioethanol production. Thirty-seven ACCd producing bacteria isolated from rhizospheric soil of field grownP. maximum and 13 were shortlisted based on their beneficial traits (root colonization, production of indole acetic acid, siderophore, hydrogen cyanide, phosphate solubilization, biofilm formation, tolerance to salt and Polyethylene glycol) and a total score obtained. All shortlisted bacteria were found significant in enhancing the plant growth, water conservation, membrane stability, biocompatible solutes and protein, phenolic contents and photosynthetic pigments in plants grown under stress conditions. Cell wall composition (Cellulose, Hemicellulose and Lignin) of the treated plants grown under stress conditions recorded a significant improvement over their respective controls and found equivalent to the plants grown under normal circumstances. Biomass from bacterial treatment recorded higher total reducing sugars upon pre-treatment and hydrolysis, and theoretical bioethanol yield.